Pertussis booster vaccine for adolescents and young adults in São Paulo, Brazil - Angela Carvalho Freitas; Valdir Okano; Júlio Cesar Rodrigues Pereira (Universidade de São Paulo, 2011)
OBJECTIVE: To develop a model to assess different strategies of pertussis booster vaccination in the city of São Paulo. METHODS: A dynamic stationary age-dependent compartmental model with waning immunity was developed. The "Who Acquires Infection from Whom" matrix was used to modeling age-dependent transmission rates. There were tested different strategies including vaccine boosters to the current vaccination schedule and three of them were reported: (i) 35% coverage at age 12, or (ii) 70% coverage at age 12, and (iii) 35% coverage at age 12 and 70% coverage at age 20 at the same time. RESULTS: The strategy (i) achieved a 59% reduction of pertussis occurrence and a 53% reduction in infants while strategy (ii) produced 76% and 63% reduction and strategy (iii) 62% and 54%, respectively. CONCLUSION: Pertussis booster vaccination at age 12 proved to be the best strategy among those tested in this study as it achieves the highest overall reduction and the greatest impact among infants who are more susceptible to pertussis complications.